Traceability in object-oriented quality engineering: A basis for regression analysis of object-oriented software. - Ben Hajla, Halim. (University of Ottawa (Canada), 1997)
Object-Oriented (O-O) technology has grown over the past decades into a well defined and increasingly popular style of programming. In this thesis, we introduce a novel method for conducing and managing regression analysis and testing activities during an O-O iterative and incremental development process. The underlying process of the method is based on the following concepts, the Method Sequence Specification (MtSS) and the Message Sequence Specification (MgSS), the class firewall and traceability. A MtSS of a class documents the causal order in which the methods can be invoked upon instantiation of the class. A MgSS for a method in a class documents the causal order in which messages can be sent to different instances of different classes. We use the MtSS and MgSS to detect the changes affecting the class specification and the interactions between classes. We introduce also a regression algorithm to solve the problem of reselection of test cases based on the class specification. Traceability links together user requirements, analysis, design, implementation models and test cases. In our proposal we used it to manage the regression analysis and testing activities and to perform change analysis. The class firewall is computed based on the class implementation affected by changes in the code. (Abstract shortened by UMI.)
Keywords: Computer Science.